Ultrathin, highly branched carbon nanotube cluster with outstanding oxygen electrocatalytic performance. (20th August 2018) - Li, Yiming; Yan, Zheng; Wang, Qiaodi; Ye, Huating; Li, Mengli; Zhu, Lianwen; Cao, Xuebo
Abstract: Metal-free heteroatom-doped porous carbons such as N, P co-doped nanoporous carbon materials with designed properties are attracting increased attention for metal-air battery applications. Herein, we report a general approach to synthesizing highly branched N, P co-doped carbon nanotube cluster (NPCTC) derived from metal-organic frameworks as a bifunctional electrocatalyst. NPCTC were obtained by treating ZIF-8 with butyl methylphosphinate, followed by two-step pyrolysis. Benefiting from the cross-linking polymerization and self-aggregation between ZIF-8 and the monomer, the resulting NPCTC exhibited higher mechanical stability and strength. Although the wall thickness was <5 nm, no obvious shrinkage and collapse were observed after graphitization, thereby maximizing the exposure of the active sites. Studies of oxygen electrocatalysis demonstrate that the NPCTC can deliver outstanding bifunctional performance with a more positive half-wave potential, higher limiting current density for oxygen reduction reaction (ORR) than Pt/C, and lower onset potential for oxygen evolution reaction (OER) than IrO2 . Homemade Zn-air battery exhibited stable charge-discharge durability over 180 cycles, with an overpotential increase of only 0.15 V. The improved electrochemical performance was mainly attributed to the synergistic effect of N, P co-doping and the distinct geometry of NPCTC, i.e., three-dimensionally interconnected hollow ultrathin nanotube branches facilitating electron and mass transfer. Graphical abstract: Image 1 Highlights: Ultrathin, highly branched carbon nanotube cluster was synthesized via a facile chemical modification strategy. Ultrathin structure favors the full utilization of catalytic active sites inside and outside the carbon nanotube cluster. The nanotube cluster demonstrates both OER and ORR activities. The enhanced activity of the nanotube cluster was associated with its morphology and co-doped N and P atoms.